The Practice of Money Politics Ahead of Elections in Hadith Review - Royan Alawi Sufyan; Dodo Widarda (Gunung Djati Conference Series, 2021)
This study aims to explain the Practice of Money Politics Ahead of the Election in Hadith Review. This research is a qualitative type that applies literature study, syarah hadith method, and content analysis. The results of this study include the understanding of money politics, in money politics, and the impact thereof, as well as politics according to hadith. This study concludes that money politics is included in risywah (bribery). In Islam, the practice of bribery is clearly prohibited. In the Qur'an, there are many who explain this, even with the words of the Messenger of Allah who explain the prohibition of risywah. Money politics is a form of action that can violate existing state laws, as well as violate sharia law. It is recommended that further research related to money politics be carried out in the form of field studies with other approaches, either in the form of direct observation during the election period or so on.